Current trends in scientific research in IT and Electrical and Electronics Engineering - Moisa, Trandafir; Grava, Cristian; Balint, Florin; Grava, Adriana-Marcela (Journal of electrical and electronics engineering, 2018)
From the vast research and development subjects in IT and Electrical and Electronics Engineering, some of the most important of them have been selected and are presented in this paper. Arguments that justify the chosen of these subjects among the most important in present are presented. The main selection criteria are the relevance for the current trends in these industries and the funding availability to insure the transition from theoretical and experimental research into practical applications. It might also help college students in shaping their preferences for a successful engineering carrier. Before approaching the specifics of the selected subjects the paper illustrates the interplay between learning strategies and scientific epistemological views to help framing an attitude toward science.